Airway malacia in premature infant twins with bronchopulmonary dysplasia: Two case reports. Issue 1 (7th January 2022) - Yang, Wanwan; Zhang, Jiuxiang; Lu, Dongxue; Zhang, Haopeng
Abstract: Premature infants who require surgery for retinopathy of prematurity often exhibit bronchopulmonary dysplasia. Reactive airway is a clinical manifestation of bronchopulmonary dysplasia. We describe premature infant twins who had difficulty with positive pressure ventilation during anesthesia. Both cases occurred during induction of anesthesia for binocular anterior chamber puncture and vitreous cavity injection. The most likely cause in each case was airway malacia. We recommend that endotracheal intubation is performed in infant patients with low body weight; the possibility of airway malacia occurrence should be considered, especially for infants with comorbid bronchopulmonary dysplasia. Abstract : Airway malacia can cause or aggravate positive pressure ventilation difficulty in premature infants with BPD, although a causal relationship cannot be conclusively established. Clinicians should consider the possibility of airway malacia occurrence in infants with low body weight, especially in the presence of comorbid BPD. For premature infant surgery, especially ophthalmology operation, tracheal intubation is safer and more reliable than supraglottic airway.